Recent Advances in Territorial Competition and Competitiveness Analysis - Daniela Luminița Constantin (Romanian Journal of European Affairs, 2006)
This paper addresses the question of territorial competitiveness – at national and regional level – from the perspective of the most important research undertaken in the international arena in order to build-up competitiveness indicators able to reveal the complexity and dynamics of this phenomenon in the contemporary society. A special emphasis is put on studies developed by prestigious organisations and research centres such as World Economic Forum, International Institute for Management Development, Cambridge Econometrics, ECORYS-NEI and so on.